PINK1/Parkin Pathway Activation for Mitochondrial Quality Control – Which Is the Best Molecular Target for Therapy? - Silvian, Laura F. (Frontiers in Aging Neuroscience, 2022)
There has been long-term interest in drugging the PINK1-Parkin pathway with therapeutics as a treatment for Parkinson’s disease(PD). Despite significant structural data on Parkin as well as the PINK1 kinase and the multiple conformational changes it undergoes, activation of these targets is nontrivial. This review highlights small molecule screening results that suggests that activation of Parkin biochemically does not necessarily translate to activation of Parkin within cells. There are also issues with activation of PINK1 with kinetin analogues, which do not appear to rescue rodent models of PD. The counter-measure of activating the mitophagy pathway with DUB inhibitors such as USP30 inhibitors is progressing in the clinic for kidney disease and the proof of biology for this target will be tested in these trials. An alternative mechanism of alerting Parkin in response to oxidative stress via Parkin phosphorylation by the AMPK-ULK1 pathway may be a simpler way to lower the basal level of Parkin activation.